PERENCANAAN AUDIT KINERJA DENGAN PENDEKATAN RISK BASED INTERNAL AUDITING PADA INSPEKTORAT JENDERAL KEMENTERIAN ESDM - PRASASTI, DEA ([Yogyakarta] : Universitas Gadjah Mada, 2015)
Audit activities in the State's financial management is conducted by external and internal government agencies regularly every year, but abnormalities are still commonly found in the management of state’s financial. In the perspective of agency theory, there is still many of irregularities were found indicating that the role of Government Internal Supervisory Apparatus (APIP) has not been effective. APIP which has the function of internal control should be able to ensure that the implementation of the procedure in accordance with government regulations. APIP has not been able to detect any irregularities or provide early warning to prevent the practice of fraud or irregularities in advance. Limited resources to carry out surveillance activities require APIP to conduct a risk assessment in assigning audit priorities. By using a risk-based internal auditing approach, auditors conduct audits based on the priorities of the organization's risk so that audits can be run effectively and efficiently. This research aims to determine whether the Inspectorate General of the Ministry of Energy and Mineral Resources has implemented a risk-based internal auditing in the preparation of the performance audit planning and the steps should be taken in applying risk based internal auditing in the planning of performance audit. In addition to a risk-based internal auditing approach, research methods is applied including data analysis, interviews and provision of scoring on the risk factors that have been set. Based on the research, revealed that the Inspectorate General of the Ministry of Energy and Mineral Resources has not fully implement risk-based internal auditing in the performance audit planning. Auditable units which have high priority to be audited are likely total lifting of petroleum; volume of mineral and coal production; the role of mineral and coal sector in regional development, through a number of Revenue Sharing Fund and Community Development Program, volume of natural gas production, total lifting of natural gas, supplies of fuel and natural gas; mineral and coal for domestic need